Apakah Social Influence Mempengaruhi Intensi Meminjam melalui Peer to Peer Lending - Agustina, Melia; Dalimunthe, Zuliani (Jurnal Manajemen dan Usahawan Indonesia, 2020)
This study aims to analyse the relationship between social influence and intention to borrow through peer to peer (P2P) lending platforms by including the factor of trust in platform as a moderating variable. P2P lending is a form of financial technology that facilitates transactions between borrowers (borrowers) and lenders (lenders) online. According to the technology acceptance model, one of the components that can influence a person to adopt new technology is social influence, how- ever, whether social influence is related to a person's intention to borrow through P2P lending platforms, especially in Indonesia, has not been widely discussed. This study uses primary data using regression analysis with the help of SPSS 20 software. Data collection took place from November to December 2018. The unit of analysis was 102 respondents who understood P2P lending. This study found that social influence has a significant positive effect on a person's intention to borrow through P2P lending. On the other hand, it is indicated that the trust factor to the platform also has a positive effect on intentions, although it cannot be said that it has a significant positive effect. What needs to consider is that there are indications that the trust factor in the platform manager is weakening the social influence relationship on borrowing intentions through the P2P lending platform.